A review on the influence of dietary immunobiotics on the performance, intestinal morphology and immune-related gene expression in post-hatched broiler chicks - Asad A. Khaskheli; Muhammad I. Khaskheli; Allah J. Khaskheli; Arshad A. Khaskheli (Aceh Journal of Animal Science, 2020)
The use of antibiotics in the broiler industry is continuously increasing for promoting growth performance, improving the edible meat yield, and preventing microbial infections in the chicks. Due to the extreme misuse of antibiotics, antimicrobial resistance is developing among the broilers and simultaneously to their consumers. Keeping in view these facts current review was planned to understand the effect of different dietary immunobiotics on the performance, intestinal morphology, and immune-related gene expression in post-hatched broiler chicks. The review of the literature indicated that the application of immunobiotics as functional foods and its biological value have been reported by many scientists worldwide. In addition, to develop immunologically functional foods, immunobiotics also help in regulating intestinal immunity. The current review further explored that the immunobiotics regulate intestinal immune homeostasis, cellular and molecular mechanisms. It was also interesting to note that immunobiotics concerning microorganisms stimulate the activation of mucosal immunity in the Gut Associated Lymphoid Tissues (GALT). In vitro studies on the toll-like receptor (TLR) 2-transfected cells showed that immunobiotics can potentially be used to enhance the immune system in the GALT. Keeping in view reviewed studies on immunobiotics it could be concluded that immunobiotics positively influence the performance, intestinal morphology, and immune-related gene expression in post-hatch chicks. They could be used as the best alternative to antibiotics. Keywords: Gut Associated Lymphoid Tissues; Immune system; Prebiotics; Receptors.